Odpowiedzi

Najlepsza Odpowiedź!
2010-01-04T22:54:56+01:00
Zad.1](2+b)³=8+12b+6b²+b³
(p-0,1)³=p³-0,3p²+0,03p-0,001
zad.2]p³-27=(p-3)(p²+3p+9)
¹/₁₂₅-v³=(⅕-v)(¹/₂₅+⅕v+v²)
pozdrawiam
2010-01-04T23:00:00+01:00
A)
(2+b)³ = 2³ + 3*2²*b + 3*2*b² + b³= 8 + 12b + 6b² + b³

(p-0,1)³ = p³ - 3*p²*(0,1) + 3p*(0,1)² - (0,1)³ = p³ - 0,3*p² + 0,03p - 0,01

b)
p³-27= p³ - 9³ = (p-9)(p²+9p+9²)= (p-9)(p²+9p+81)

1/125-v³ = 1/(5³-v³)= 1/(5-v)(25+5v+v²)
2010-01-04T23:02:05+01:00
1Zapisz w postaci sumy algebraicznej:
(2+b)³=8+3*4b+3*2b²+b³=8+12b+6b²+b³

(p-0,1)³=p³-3*p²*0,1+3*p*0,01-0,001=p³-0,3p²+0,03p-0,001
2.Zapisz w postaci iloczynu:
p³-27=(p-3)(p²+3p+9)
1/125-v³=(1/5 -v)(1/25 +1/5 v +v²)